2019
DOI: 10.1111/jan.14136
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and characteristics of clinical subtypes of perinatal depressive symptoms: A latent class analysis

Abstract: Aims To investigate clinically relevant subtypes of perinatal depressive symptoms. Design Cross‐sectional study. Methods A sample of 2,783 women at different prenatal and postnatal periods was recruited between August 2015 – August 2017. The Patient Health Questionnaire–9 (PHQ‐9) was used to assess depressive symptoms. Data analyses consisted of latent class analysis (LCA), analysis of variance and multinomial logistic regression. Results (a) Five latent subtypes (Classes 5/4/3/1/2) were identified: ‘no sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
(86 reference statements)
1
27
0
Order By: Relevance
“…These findings provided evidence for the external validity of the distinction between the MDD somatic and non-somatic factors. Third, the two-factor model could be better interpreted as different symptomatic representation and subtypes of MDD than the unidimensional model [50,51]. A number of empirical studies used machine learning, genetic, and biological approaches to yield strong evidence in favor of MDD consisting of somatic and affective/cognitive factors, rather than one "depression" factor [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…These findings provided evidence for the external validity of the distinction between the MDD somatic and non-somatic factors. Third, the two-factor model could be better interpreted as different symptomatic representation and subtypes of MDD than the unidimensional model [50,51]. A number of empirical studies used machine learning, genetic, and biological approaches to yield strong evidence in favor of MDD consisting of somatic and affective/cognitive factors, rather than one "depression" factor [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries, the prevalence of antenatal and postnatal depression varies between 7 and 15% [ 2 ], and between 19 and 25% in low-income countries [ 3 ]. PND is considered one of the most common complications of pregnancy and has a significant impact on the mother, her offspring and even her entire family [ 4 , 5 ]. When not treated properly, PND has a negative impact on the outcome of childbirth [ 6 ], the child’s health, and their social and emotional development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have also found an anxiety subscale within the EPDS (e.g., Loyal et al, 2020), and indeed, comorbidity between anxiety and depressive symptoms during the postpartum period has been reported in the literature (Falah‐Hassani et al, 2016). Thus, heterogeneity in PPD symptoms should also be understood in light of both anhedonia and anxiety symptoms, in addition to depressive symptoms (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%